Upgrading biomethane for low carbon fuel - Mel, Maizirwan; Mohd Ghauth, Nor Farhana; Ithnin, Mohamad Hafiz; Mohamad Fozi, Aidil Azim; Salleh, Md Noor; Ihsan, Sany Izan; Hassan, Md Sadikin (Ministry of Higher Education Malaysia (MOHE), 2017)
Biomethane is a result of the process removing of the CO2 in the biogas to get the high purity of methane content up to 97% using the adsorption process. This technology could be potential to use in the fuel production as nowadays the production of fuel was slowly depleted. Biomethane is one of the sources that closely resembling the natural gas to act as a source of energy to rural areas and has been researched for many years due to their potential as renewable energy for future. There are several methods that have been developed to increase the purity of biomethane such as chemical/physical absorption, water scrubbing, membrane separation and pressure swing adsorption (PSA). The demand of the technologies for biomethane upgrading in industries keeps increasing by year as used as vehicle fuel. The PSA method has been focused in this project. The method was used to increase the content of biomethane to reduce the amount of carbon dioxide in the gases and to eliminate some impurities. The PSA system basically use the application of the absorbent such as activated carbon and molecular sieve at high pressure condition in adsorption column. It is proved that the PSA method is a good method to separate the CO2 from the biogas to get high content of methane (over 90%) using selected adsorbent. By using the upgrading technologies process will give the opportunities to develop high quality production of biomethane with environmentally friendly and lower operational cost.